2022
DOI: 10.1111/ijfs.15925
|View full text |Cite
|
Sign up to set email alerts
|

Pressurised hot water extraction of phenolic compounds with a focus on eriocitrin and hesperidin from lemon peel

Abstract: Summary In this study, the extraction of bioactive compounds from lemon peel, a by‐product of the food industry, was investigated using pressurised hot water extraction (PHWE) at different extraction temperatures (40–200 °C) and times (5–30 min) under 10.34 MPa pressure. The selectivity of the PHWE process on eriocitrin and hesperidin extraction was also tested. The highest total phenolic content (TPC) (59.57 mg gallic acid equivalents g−1), total flavonoid content (TFC) (8.22 mg catechin equivalents g−1) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 38 publications
(55 reference statements)
2
6
0
Order By: Relevance
“…For undigested orange peels, hesperidin was determined as the predominant flavonoid accounting for 50–74% of the total flavonoids, whereas for undigested lemon peels, eriocitrin was the dominant flavonoid, representing 59–67% of the total flavonoids. These findings are in agreement with previous studies that reported hesperidin and eriocitrin as the main flavonoids in orange and lemon peels, respectively 37,38 . After oral digestion, lower levels of flavonoids were obtained compared with undigested samples, and release of flavonoids increased following gastric digestion.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…For undigested orange peels, hesperidin was determined as the predominant flavonoid accounting for 50–74% of the total flavonoids, whereas for undigested lemon peels, eriocitrin was the dominant flavonoid, representing 59–67% of the total flavonoids. These findings are in agreement with previous studies that reported hesperidin and eriocitrin as the main flavonoids in orange and lemon peels, respectively 37,38 . After oral digestion, lower levels of flavonoids were obtained compared with undigested samples, and release of flavonoids increased following gastric digestion.…”
Section: Resultssupporting
confidence: 93%
“…These findings are in agreement with previous studies that reported hesperidin and eriocitrin as the main flavonoids in orange and lemon peels, respectively. 37,38 After oral digestion, lower levels of flavonoids were obtained compared with undigested samples, and release of flavonoids increased following gastric digestion. Intestinal digestion generally further enhanced the flavonoid levels of lemon peels.…”
Section: Resultsmentioning
confidence: 99%
“…The highest extraction yield (22.61%) and total phenolic content (7.6 mg GAE/g of raw materials RM) were obtained at 180 °C. Similar facts about the extraction yield and total phenolic content increasing with temperature have been extensively observed in PHWE studies and are explained by the increasing mass transfer, lower surface tension, and higher solubility of numerous compounds resulting from the increased temperature [ 43 , 44 , 45 ].…”
Section: Resultssupporting
confidence: 70%
“…They observed that corn silk polysaccharide could induce nitric oxide production, phagocytosis index, and acid phosphatase activity in a dose-dependent manner in RAW264.7 cells. Alasalvar et al (2023) observed an improvement in the extraction yield of eriocitrin and hesperidin from lemon peel following pressurised hot water extraction by controlling temperature and time. Meanwhile, Kumar et al (2023) applied a combination of emerging technologies for the extraction of lycopene from tomato processing waste only to find an increase in extraction yield.…”
mentioning
confidence: 96%
“…Alasalvar et al . (2023) observed an improvement in the extraction yield of eriocitrin and hesperidin from lemon peel following pressurised hot water extraction by controlling temperature and time. Meanwhile, Kumar et al .…”
mentioning
confidence: 99%